2015
DOI: 10.1051/0004-6361/201525847
|View full text |Cite
|
Sign up to set email alerts
|

26Al kinematics: superbubbles following the spiral arms?

Abstract: Context. High-energy resolution spectroscopy of the 1.8 MeV radioactive decay line of 26 Al with the SPI instrument onboard the INTEGRAL satellite has recently revealed that diffuse 26 Al has higher velocities than other components of the interstellar medium in the Milky Way. 26 Al shows Galactic rotation in the same sense as the stars and other gas tracers, but reaches excess velocities of up to 300 km s −1 . Aims. We investigate whether this result can be understood in the context of superbubbles, taking i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(77 citation statements)
references
References 62 publications
9
67
1
Order By: Relevance
“…The Eridanus cavity presents a viewing geometry similar to what we propose for massive star groups in the Galaxy's spiral arms to explain the large excess above Galactic rotation velocities [5,6]. Fitting a Gaussian line shape to the Orion 26 Al γ-ray signal, the line width is found to be compatible with the instrumental resolution, and it is indicated (hatched region in Fig.…”
Section: The Orion Regionsupporting
confidence: 63%
See 1 more Smart Citation
“…The Eridanus cavity presents a viewing geometry similar to what we propose for massive star groups in the Galaxy's spiral arms to explain the large excess above Galactic rotation velocities [5,6]. Fitting a Gaussian line shape to the Orion 26 Al γ-ray signal, the line width is found to be compatible with the instrumental resolution, and it is indicated (hatched region in Fig.…”
Section: The Orion Regionsupporting
confidence: 63%
“…Measurements of systematic Doppler shifts of the line with Galactic longitude [4,5] had shown that the observed 26 Al γ rays originate from sources throughout the Galaxy, including its distant and otherwise occulted regions at and beyond the inner spiral arms and bulge. Moreover, the Doppler shifts of the 26 Al-line centroid energy were found larger than expected from large-scale Galactic rotation, and suggested that large cavities around massive star groups play a major role in guiding ejecta flows from massive-star and supernova nucleosynthesis [6,7].…”
Section: Introductionmentioning
confidence: 93%
“…High energy resolution γ-ray spectroscopy reveals that 26 Al rotates in the same general sense as the Galaxy but has large velocities in comparison to other components of the ISM. Krause et al (2015) explore the hypothesis that this behavior can be explained from the kinematics of "superbubbles" created by the correlated SN explosions mixing the ejecta into the hot phase of the ISM. By contrast, the delay time of NSM should result in uncorrelated activity and therefore the kinematics could be substantially different.…”
Section: Diffuse Emissionmentioning
confidence: 99%
“…INTEGRAL/SPI data for the 1809 keV 26 Al line suggest that on the global, Galactic scale, superbubbles are key structures in the transport of fresh ejecta towards new star forming regions [86,87]. With its huge increase in sensitivity, e-ASTROGAM will provide a detailed view of the morphology of this emission, with high precision measurements of the line flux from many regions of the Galaxy.…”
Section: Nova Explosionsmentioning
confidence: 99%